2016
DOI: 10.1017/pao.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex PCR test to identify four common cattle-adapted Cryptosporidium species

Abstract: S U M M A R YCryptosporidium is a well-known cause of neonatal enteritis in cattle worldwide. Cattle are commonly infected with four different species of Cryptosporidium but only one of these, Cryptosporidium parvum, is associated with clinical disease. Identification of species in cases of calf scour can give an indication if Cryptosporidium is the causative agent or not. In addition, C. parvum is a zoonotic species and so has implications for human health, for this reason it is important to identify the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
3
21
0
1
Order By: Relevance
“…This method therefore captured the severity of the disease by including only the disease timeframe (G. Innocent, BiOSS, Personal Communication). In addition, Bueno da Silva et al (2019) used microscopy to determine oocyst concentration, whereas the current study used 18S nested species-specific PCR (Thomson et al, 2016), allowing speciation of Cryptosporidium and determination that the oocysts present were C. parvum. The results from this study are in contrast to a study looking at growth rates in dairy calves with and without diarrhoea in New York (Virtala et al, 1996), which found no significant difference in growth rates between the two groups of calves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method therefore captured the severity of the disease by including only the disease timeframe (G. Innocent, BiOSS, Personal Communication). In addition, Bueno da Silva et al (2019) used microscopy to determine oocyst concentration, whereas the current study used 18S nested species-specific PCR (Thomson et al, 2016), allowing speciation of Cryptosporidium and determination that the oocysts present were C. parvum. The results from this study are in contrast to a study looking at growth rates in dairy calves with and without diarrhoea in New York (Virtala et al, 1996), which found no significant difference in growth rates between the two groups of calves.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium spp. were identified using a multiplex PCR (Thomson et al, 2016), amplifying the 18S region, including specific primers for species commonly found in cattle, namely C. parvum, Cryptosporidium bovis, Cryptosporidium ryanae and Cryptosporidium andersoni. Any C. parvumpositive samples were genotyped at the gp60 gene and loci MM5, MM18, MM19 and TP14 (Morrison et al, 2008;Hotchkiss et al, 2015) to determine the multilocus genotypes of the affected calves.…”
Section: Diagnosis and Genotyping Of Cryptosporidiummentioning
confidence: 99%
“…Amplification of DNA was by nested PCR targeting the 18S gene [19]. Briefly, each 25 μL reaction contained 10 × PCR buffer (45 mM Tris–HCl pH 8.8, 11 mM (NH4)2SO 4 , 4.5 mM MgCl 2 , 4.4 μM EDTA, 113 μg mL −1 BSA, 1 mM each of four deoxyribonucleotide triphosphates), 0.5 units BioTaq (BIO-21040, Bioline, London, UK) and 10 μM of each primer.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular assays are essential to give further information on parasite species and genotype [38]. Different Cryptosporidium species can be detected using multiplex PCR assays [39] or by direct sequencing but this is not done as a routine diagnostic test. Molecular-based diagnostics are widely used in commercial labs, often using real time PCR (that is helpful to detect low concentrations of oocysts) and are increasingly used in human diagnostics.…”
Section: Transmission Of Cryptosporidiummentioning
confidence: 99%